2021
DOI: 10.4102/safp.v63i1.5357
|View full text |Cite
|
Sign up to set email alerts
|

Preanaesthetic assessment and management in the context of the district hospital

Abstract: Preanaesthetic assessment and management allow for the systematic identification of perioperative risks and the implementation of interventions to mitigate them, such that the patient’s physiological state is optimised for surgery or other procedures. This is a crucial activity for good perioperative outcomes, as patients not assessed are at a higher risk of unanticipated adverse perioperative events and are more likely to receive suboptimal management. The district hospitals in South Africa perform minor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The secondary objective is to advise premedication drugs and perform any interventions required before surgery. [ 1 ] An important requirement for risk assessment is to order investigations on an individual basis and obtain referrals from other specialities. Effective preoperative assessment can decrease delay and postponement of the surgery on the day of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary objective is to advise premedication drugs and perform any interventions required before surgery. [ 1 ] An important requirement for risk assessment is to order investigations on an individual basis and obtain referrals from other specialities. Effective preoperative assessment can decrease delay and postponement of the surgery on the day of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of pre‐anaesthetic assessment are to reduce patient's surgical and anaesthetic risk of perioperative morbidity, mortality and to return the patient to a desirable functioning as quickly as possible. Pre‐anaesthetic assessment includes evaluation of the patient's medical status and ability to tolerate anaesthesia for the planned procedure, obtaining knowledge of the clinical characteristics of the patients, and preparing the patient for the procedure 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Pre-anaesthetic assessment includes evaluation of the patient's medical status and ability to tolerate anaesthesia for the planned procedure, obtaining knowledge of the clinical characteristics of the patients, and preparing the patient for the procedure. 3,4 It has been shown that pre-anaesthetic assessment may reduce patient anxiety regarding perioperative care, rate of surgery, cancellation or postponement, and length of hospital stay. 5 Moreover, the omission of pre-anaesthetic assessment is associated with, for example, a higher risk of unanticipated adverse perioperative events and a negative impact on patient outcomes.…”
Section: Introduction 1| Rationalementioning
confidence: 99%
“…POC testing which can be done at the patient’s bedside or in a satellite laboratory is fast evolving; eg- dipsticks for urine analysis, hand-held glucometers for blood glucose, viscoelastic haemostatic assays withTEG ® 6s for functional fibrinogen level and rapid thromboelastography, instant non-invasive spectrophotometer for haemoglobin, POC tests for pregnancy, blood gases, electrolytes, troponin and infectious diseases. [ 20 21 22 23 ] POC testing though simple, provides results in real-time and is less risky to use, and can be associated with errors. [ 20 ] POC testing may help to minimise preoperative investigations in the future.…”
mentioning
confidence: 99%